The correlations of nicotine addiction with the levels of impulsiveness, depression and anxiety in obsessive-compulsive patients - Tan, Oğuz; Hızlı Sayar, Gökben; Ünsalver, Barış Önen; Arat, Murat Mustafa; Karamustafalıoğlu, Oğuz (Journal of Dependence, 2014)
Objective: Few studies comparing smoking and non-smoking obsessive compulsive disorder (OCD) patients have found results contradicting research on other anxiety disorders. OCD is a disorder with compulsive and impulsive features. Investigating the relationships among addiction, compulsivity and impulsiveness might contribute to the understanding of the interaction of those concepts.Method: This study compared impulsiveness in smoking and non-smoking OCD patients. Then, we measured the correlations among the severities of impulsiveness, OCD and addiction. Depressive symptoms and anxiety were also included in the analysis since they are frequently accompanied by OCD, addictive disorders and pathological conditions characterized by high impulsiveness. Patients with OCD (n=121) were given Yale-Brown Obsessive Compulsive Scale (Y-BOCS), Barratt Impulsiveness Scale-Version 11 (BIS-11), Fagers-tröm Test for Nicotine Dependence (FTND), Hamilton Depression Rating Scale-17 Item (HDRS-17) and Beck Anxiety Inventory (BAI).Results: The prevalence of smoking was 42.14 %. The current and never-smokers did not show any statistically significant differences regarding the scores of the Y-BOCS, HDRS-17, and BAI. The BIS-11 total and nonplanning subscales were significantly higher in the current smokers. The Y-BOCS scores showed a positive correlation with the BIS total, cognitive, and non-planning scores only in the current smokers. Only in the smokers, the compulsion scores showed a positive correlation with the BIS-11 total and cognitive impulsiveness subscale. The FTND scores were correlated with the scores of the BIS-11 total and of the subscales of behavioral impulsiveness and non-planning. The FTND scores were also correlated with the scores of the Y-BOCS and BAI but not with the HDRS-17.Conclusion: More severe OCD in more impulsive smokers is related to higher compulsivity rather than obsessiveness, supporting the relationship among compulsivity, impulsiveness, and addiction.
Keywords: Obsessive-compulsive disorder; nicotine addiction; impulsiveness; anxiety; depressive symptoms